ESC/EAS guidelines for the detection, prevention, and treatment of individuals at risk of a first myocardial infarction: effect of 5 years of updates and the new SCORE2. Issue 6 (5th April 2022) - Sulman, David; Zeitouni, Michel; Silvain, Johanne; Kerneis, Mathieu; Guedeney, Paul; Barthélémy, Olivier; Brugier, Delphine; Sabouret, Pierre; Lattuca, Benoit; Mertens, Emilie; Posson, Julianne; Procopi, Niki; et al.
Abstract: Aims: The European Society of Cardiology (ESC) has released three consecutive guidelines within 5 years addressing cardiovascular prevention, risk scores, and cholesterol treatment. This study aims to evaluate whether the 2021 ESC guidelines improved the eligibility of individuals for primary prevention statin therapy before their first ST-segment elevation myocardial infarction (STEMI), and for intensive lipid-lowering treatments in secondary prevention. Methods and results: The cardiovascular risk category of 2757 consecutive individuals admitted for a first STEMI was evaluated to assess whether they would have been eligible for primary prevention statins according to 2021 vs. 2019 and 2016 ESC guidelines. Eligibility for intensive lipid-lowering therapy in secondary prevention was assessed according to the real-life follow-up low-density lipoprotein cholesterol (LDL-C) and the expected follow-up LDL-C. More individuals would have been eligible for primary prevention statins according to 2021 and 2019 vs. 2016 guidelines (61.8% vs. 38.7% vs. 23.6%, P < 0.01), a finding observed in both men (62.3% vs. 35.0% vs. 24.9%, P < 0.01) and women (60.2% vs. 50.7% vs. 19.3%, P = 0.18). Only 27% of individuals reached the LDL-C objective of 55 mg/L in secondary prevention: using the ESC stepwise approach, 61.7% were eligible for higher doses of statins, 26.2% for ezetimibe, and 12.1% for a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor (PCSK9i). Based on expected LDL-C reductions, eligibility for a PCSK9i in secondary prevention was greater with 2021 vs. 2016 guidelines (44.5% vs. 22.5%, P < 0.01). Conclusion: The 2021 ESC guidelines improved the detection and treatment of individuals at risk for a first myocardial infarction. In secondary prevention, 70% of patients kept LDL-C levels above 55 mg/dL: increasing the statin dose and adding ezetimibe were the most frequently recommended therapeutic actions. Graphical Abstract: